Beyond the gender (dis)empowerment dichotomy : the double-faceted role of mobile phone use in gender struggles of Chinese female rural-urban migrant workers - Pei, Xin (2019)
Over the past two decades, the global diffusion of the mobile phone is accompanied by its deepening integration into varied aspects of daily life and work of socially marginalized women of the developing nations. Great attention has been subsequently drawn to the gender impacts arising from these women’s mobile phone adoptions and practices. The extant scholarly discussion has trended towards a gender (dis)empowerment dichotomy – equating the phone either as the empowerment tool that generated the immediate arrival of gender equality, or the threat towards reinforced patriarchal oppression. However, this prevailing dichotomy embodies a static nature of viewing these marginalized women in the binary of either feminist agents capable of deploying the phone for overt resistances, or powerless victims whose mobile practices centered on fulfilling traditional gender expectations. This dichotomy exhibits its theoretical limitation in examining mobile phone use by the group of female rural-urban migrant workers in the context of reformed post-Mao China. The encounters between the authoritarian socialist regime and western capitalist modernity at the societal level contribute to the continual gender struggles of these migrant women between obedience to traditional gender norms and the pursuit for modern desires. Therefore, beyond the dichotomy, it becomes necessary to capture the contextually situated and dynamically negotiated role played by the phone in these struggles. The intersectionality perspective (Brah & Phoenix, 2004; Collins, 2002; Crenshaw, 1989; Hooks, 1981), bridged with theory of structuration (Giddens, 1984), provide this thesis with a lens to examine the role of the mobile phone in the interactions between the agency of women to get empowered, and their situated social structures. Qualitative data drawn upon interviews with forty-three female migrant workers, and observation extending from their workplace, living spaces, to mobile spaces, allowed this thesis to unfold the double-faceted role of mobile phone use that simultaneously constrains and empowers women, across their personal and professional spheres. To specify, mobile phone use enables the reinforcement of social structural constraints to suppress women’s agency through three progressive steps – identification, surveillance, and intervention. The progressive nature of the steps arises conceptually from the increasing levels of intrusion and control, rather than as a sequential series. First, the channels required to identify women are enforced. Next comes surveillance, the close observations of women’s daily gender practices. Finally, the mobile-enabled intervention aims to place women under absolute control. There is an opposing process in contradiction with that of intersectional socio-structural forces depressing agency. This thesis proposes the second part of the theoretical framework in which agency acts on structures via mobile phone use in four successive ways – avoidance, accommodation, personal development, and collaboration. Rather than strictly following a chronological order, the sequence reflects the successively strengthened agency of women to strive for freedom in expression and personal choices. In its simplest form, avoidance is a means of protecting oneself from surveillance and control without confrontation. However, when one cannot avoid, accommodation is a strategy where obedience is superficially manifest as a moral cover to justify one’s pursuit of personal interests and desires. Closely accompanying this lies the engagement in personal development. Finally, collaboration clusters individuals in small groups to share social and informational support, moving towards the emergence of collective female power. The constraining yet empowering processes arising from mobile phone use are observed as socially catalyzing gender transformation of these marginalized migrant women in China across individual, interactional, and institutional levels. At the individual level, mobile phone use facilitates women’s embrace of self-consciousness. The mobile mediated connection further leverages the individual shifts into interactional-level collaboration, which in succession engages women into the discursive and practical construction and negotiation of their unique gender culture. The institutional structural transformation exhibits an asymmetry of “continuity and change” (Tacoli, 1999: 658). While the continuity lies in mobile practices that sustain structural rules via facilitating access to women for a further imposing of surveillance and intervention, the change stems out of women’s mobile phone use to alter and re-shape their situated institutional structures with the purpose of addressing their discursive power and decision-making power. In general, the theoretical implication of this thesis goes beyond the context of post-Mao China to advance literature upon the encounters between the globally diffused mobile phone and socially marginalized women of vast developing nations, whose gender construction trajectories, akin to these Chinese migrant women, have been tremendously re-shaped by the clashes and convergences between traditionally rooted social orders and globally penetrated western capitalist modernity in their local contexts.